2020
DOI: 10.1111/pbaf.12271
|View full text |Cite
|
Sign up to set email alerts
|

The Lure of New Jobs: How Framing Impacts Perceptions of Local Subsidies for Sports Teams

Abstract: Municipalities often use public funds to support private projects in pursuit of economic growth or improved quality of life. How does the framing of municipal subsidies impact public support for such funding? We examine the case of government‐funded minor league baseball stadiums to address this question. Using nationally representative survey data, we find respondents are much more likely to support funding for stadiums when told that baseball will bring jobs and improve the local economy, compared to other f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Researchers have found that framing stadiums as economic development projects is persuasive; therefore, it is unsurprising that stadium proponents often promote their fiscal potency as the primary justification for public subsidies (Connolly and Touchton 2020). Though common mistakes of commissioned economic impact analyses are well documented, professional consultant studies appear to be effective in promoting the stadium funding.…”
Section: Evaluation Frameworkmentioning
confidence: 99%
“…Researchers have found that framing stadiums as economic development projects is persuasive; therefore, it is unsurprising that stadium proponents often promote their fiscal potency as the primary justification for public subsidies (Connolly and Touchton 2020). Though common mistakes of commissioned economic impact analyses are well documented, professional consultant studies appear to be effective in promoting the stadium funding.…”
Section: Evaluation Frameworkmentioning
confidence: 99%
“…Professional consulting firms often produce these advocacy reports, but moonlighting academic researchers and university‐affiliated centers are often contracted to lend credibility to the report's dubious conclusions. Stadium boosters likely commission private economic impact reports because voters view public funding of stadiums more favorably when they are framed as economic development catalysts (Connolly & Touchton, 2020). Commissioned impact studies are promoted to the community, local media, local growth coalition members, and elected representatives as proof of a stadium's favorable economic prospects.…”
Section: Explaining the Disconnect Between Research And Policy Decisionsmentioning
confidence: 99%
“…Stadium boosters often hire consultants to conduct economic or fiscal impact analyses that demonstrate the proposed sports development will generate large returns to the community through increased economic activity, creating jobs and wealth in the community while growing the tax base to pay for itself through increased tax collections. These reports are part of what Coates and Humphreys (2008) describe as a “promotional literature.” These reports are often released at the same time the stadium project is announced, because economic development justifications are persuasive in fostering favorable public perceptions of sports facility subsidies (Connolly & Touchton, 2020). Delaney and Eckstein (2008) provide examples of how local media outlets often present advocacy studies uncritically or provide false balance to more credible academic studies, which can influence public perceptions.…”
Section: The Public Funding Paradoxmentioning
confidence: 99%
“…These reports are part of what Coates and Humphreys (2008) describe as a "promotional literature." These reports are often released at the same time the stadium project is announced, because economic development justifications are persuasive in fostering favorable public perceptions of sports facility subsidies (Connolly & Touchton, 2020). Delaney and Eckstein (2008) provide examples of how local media outlets often present advocacy studies uncritically or provide false balance to more credible academic studies, which can influence public perceptions.…”
Section: High-profile Advocacy Reportsmentioning
confidence: 99%